Argostemma laotica (Rubiaceae), a new species from Laos - Lanorsavanh, Soulivanh; Chantaranothai, Pranom (Phytotaxa, 2016)
Argostemma laotica, a new species from Laos, is described and illustrated. The species appears most similar to A. concinnum but differs in having pubescent stem, corolla and ovaries, oblique leaf base, shorter pedicel and smaller anthers which a dehiscence by an apical pore. The conservation status of this new species is vulnerable (VU D2).